2022
DOI: 10.1017/s2045796022000683
|View full text |Cite
|
Sign up to set email alerts
|

Global trends and regional differences in the burden of anxiety disorders and major depressive disorder attributed to bullying victimisation in 204 countries and territories, 1999–2019: an analysis of the Global Burden of Disease Study

Abstract: Aim This study aimed to analyse the temporal and spatial trends in the burden of anxiety disorders and major depressive disorder related to bullying victimisation on global, regional and country scales. Methods Data were from the 2019 Global Burden of Disease (GBD) Study. We assessed the global disability-adjusted life years (DALYs, per 100 000 population) of anxiety disorders and major depressive disorder attributable to bullying victimisation by age, sex and geographical location. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In general, females have been shown to be more vulnerable to the psychological consequences of stress, such as depression and anxiety, in that they generally seem to be at higher risk for developing these disorders (Hankin et al, 2007; Seedat et al, 2009; Tolin & Foa, 2006). It is important to note that other factors such as culture and race and ethnicity also contribute to sex‐specific vulnerability to psychopathology (Hong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In general, females have been shown to be more vulnerable to the psychological consequences of stress, such as depression and anxiety, in that they generally seem to be at higher risk for developing these disorders (Hankin et al, 2007; Seedat et al, 2009; Tolin & Foa, 2006). It is important to note that other factors such as culture and race and ethnicity also contribute to sex‐specific vulnerability to psychopathology (Hong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Some might argue that if limited resources are to be allocated to the social determinants of mental health, these should focus on those social determinants for which mental health is particularly relevant, in a way that might not be the case for other health conditions. An example might be that of bullying, which may not be a major social determinant of health, but has been shown to be a powerful and growing predictor of poor mental health in the global burden of disease study ( Hong et al, 2022 ).…”
Section: Policy Challengesmentioning
confidence: 99%
“…Moreover, there was a paucity of studies on the proportions of MDD burden attributed to modifiable risk factors (e.g., IPV, CSA and BV), though one study reported the burden of MDD caused by BV (Hong et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%